2018
DOI: 10.3233/jpd-181327
|View full text |Cite
|
Sign up to set email alerts
|

Stomaching the Possibility of a Pathogenic Role for Helicobacter pylori in Parkinson’s Disease

Abstract: While a small subset of Parkinson’s disease cases have genetic causes, most cases are sporadic and may have an environmental contributor that has largely remained enigmatic. Remarkably, gastrointestinal symptoms in PD patients serve as a prodrome for the eventual motor dysfunctions. Herein, we review studies exploring a possible link between the gastric human pathogen Helicobacter pylori and PD. We provide plausible and testable hypotheses for how this organism might contribute to PD: 1) a toxin(s) produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 76 publications
2
53
0
Order By: Relevance
“…The results of the present study are in agreement with previous research indicating the association between H. pylori and dementia or neurodegenerative disorders [3-5, 7, 15, 35]. H. pylori infection is associated with higher risk of Alzheimer's disease, vascular dementia, Parkinson's disease, and neuromyelitis optica [14,[36][37][38][39][40][41][42]. However, the contribution of H. pylori to the development of neurodegeneration showing speci c topography of cortical thinning, was not previously reported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study are in agreement with previous research indicating the association between H. pylori and dementia or neurodegenerative disorders [3-5, 7, 15, 35]. H. pylori infection is associated with higher risk of Alzheimer's disease, vascular dementia, Parkinson's disease, and neuromyelitis optica [14,[36][37][38][39][40][41][42]. However, the contribution of H. pylori to the development of neurodegeneration showing speci c topography of cortical thinning, was not previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…Second, H. pylori-related metabolic dysfunction can increase the risk of cardiovascular disease which in turn increases the risk of Alzheimer's disease [12,13]. Third, H. pylori can directly damage the central nervous system (CNS) by producing toxic materials [14] or by mechanically invading the CNS through gastrointestinal tract-associated retrograde axonal transport pathway or H. pylori-infected monocyte circulation [15]. Finally, H. pylori induces dysbiosis of microbiota in the gastrointestinal tract that alters the gut-brain-axis toward neurodegenerative cascade [3,16].…”
Section: Introductionmentioning
confidence: 99%
“…A gastric disorder that is seen with increased frequency in PD and that can contribute to impairment of oral levodopa absorption is H. pylori infection, which also is associated with ulcers, gastritis, and gastric cancer [78]. H. pylori may be diagnosed noninvasively with a urea breath test, stool antigen test, or serological tests, of which the most accurate and widely used is an enzyme-linked immunosorbent assay, or invasively with histologic analysis of endoscopic biopsy samples or rapid urease testing of biopsy specimens [79].…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…H. pylori may be diagnosed noninvasively with a urea breath test, stool antigen test, or serological tests, of which the most accurate and widely used is an enzyme-linked immunosorbent assay, or invasively with histologic analysis of endoscopic biopsy samples or rapid urease testing of biopsy specimens [79]. Studies and meta-analysis data, collectively involving > 40,000 patients, have found that H. pylori infection is associated with an estimated two-to three-fold higher incidence of PD versus matched controls without infection [78,[80][81][82]. Prevalence of H. pylori in patients with PD appears to be~32-70% [78].…”
Section: Helicobacter Pylorimentioning
confidence: 99%
See 1 more Smart Citation